Racial differences in experimental pain sensitivity and conditioned pain modulation: a study of Chinese and Indians - Ng TS (Journal of Pain Research, 2019)
Tze Siong NgDepartment of Rehabilitation, Physiotherapy Section, National University Hospital, Singapore, SingaporeBackground: Substantial literature has demonstrated racial differences in pain perception and endogenous pain modulation is proposed to be a mechanism for the racial differences. Although Indians in Singapore reported higher pain severity than Chinese, the only study on racial difference in experimental pain response in Singapore did not find any difference between the two racial groups.Purpose: The aim of this study was to investigate pain sensitivity and conditioned pain modulation in Chinese and Indians in Singapore.Patients and methods: Sixty age-and sex-matched (30 Chinese 50% female, 30 Indian, 50% female) healthy adults participated in this study. Pressure pain threshold, thermal pain threshold and cold pain tolerance were measured. Conditioned pain modulation, general self-efficacy and depression were also tested, in an attempt to assess endogenous pain inhibition and psychological presentation between the two groups.Results: No difference in pain thresholds was found between the two groups. Indians demonstrated less cold pain tolerance and less efficacious conditioned pain modulation than Chinese. Conditioned pain modulation was a mediator between race and cold pain tolerance.Conclusion: These findings of racial disparities in pain tolerance and endogenous pain inhibition could possibly contribute to the higher pain severity in Indians.Keywords: pain tolerance, race, general self-efficacy